Food preferences of college students in Roxas City in terms of macronutrients. - Almeida, Abegail Dela Cruz
The fundamental understanding in consumer's food preferences may lead to the promotion of heathy eating habits. Through surveys conducted in the study, Spearman rank revealed no significant correlation between the respondent's carbohydrates preference and age (rS=-0.03, p=0.74), as well as Facebook (FB) usage (rS=-0.13, p=0.12). Similarly, protein preference shows no significant correlation with age (rS=0.04, p=0.64) and FB usage (rS=0.07, p=0.43). Likewise, fats preference demonstrates no significant correlation with age (rS=-0.05, p=0.54) and FB usage (rS=-0.10, p=0.21). Gamma correlation analysis revealed no significant correlation between carbohydrates preference and sex (=-0.06, p=0.63), as well as protein preference and sex (=-0.20, p=0.13). Similarly, food preference in fats show no significant correlation with sex (=-0.02, p=0.86). These non-significant correlations suggest that there is no substantial association between the food preferences and the demographic variables of sex, age, and FB usage in the population. Moreover, Friedman test revealed that carbohydrates is the most preferred macronutrient with the highest mean rank of 2.11. Data collected can be utilized to produce products that are not just appealing to consumer's tastes, but also healthier.